2014
DOI: 10.1021/ac502133r
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Water Infusion Enhances Atmospheric Pressure Chemical Ionization of Methyl Chloroformate Derivatives in Gas Chromatography Coupled to Time-of-Flight Mass Spectrometry-Based Metabolomics

Abstract: The effects of continuous water infusion on efficiency and repeatability of atmospheric pressure chemical ionization of both methyl chloroformate (MCF) and methoxime-trimethylsilyl (MO-TMS) derivatives of metabolites were evaluated using gas chromatography-time-of-flight mass spectrometry. Water infusion at a flow-rate of 0.4 mL/h yielded not only an average 16.6-fold increase in intensity of the quasimolecular ion for 20 MCF-derivatized metabolite standards through suppression of in-source fragmentation but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The respective masses m / z 215.1469, 177.0947 and 147.0844 could be explained as the adduction of a water molecule to these fragments. The inclusion of a small amount of water in the APCI source to promote the formation of the [M + H] + could explain this phenomenon as already described by Wachsmuth et al . Therefore, dicyclopentyl‐dimethoxysilane was retained as the probably identified migrant.…”
Section: Resultssupporting
confidence: 90%
“…The respective masses m / z 215.1469, 177.0947 and 147.0844 could be explained as the adduction of a water molecule to these fragments. The inclusion of a small amount of water in the APCI source to promote the formation of the [M + H] + could explain this phenomenon as already described by Wachsmuth et al . Therefore, dicyclopentyl‐dimethoxysilane was retained as the probably identified migrant.…”
Section: Resultssupporting
confidence: 90%
“…The highest suppression was approximately 40% for most compounds in apple [4]. Secondly, GC-APCI is less reproducible in comparison with GC-EI, but the work of Wachsmuth et al [37] shows a nice increase in reproducibility by water infusion into the APCI ion source.…”
Section: Combination Of Apci and Eimentioning
confidence: 97%
“…A higher concentration of water into the APCI source by a syringe pump significantly increases the sensitivity and selectivity. Wachsmuth et al [37] reported not only an average 16.6-fold increase in intensity of the protonated molecule for 20 derivatized metabolite standards through the reduction of in-source fragmentation, but also the most repeatable peak area integrals by water infusion at a flow-rate of 0.4 mL/h. Ionization of analytes occurs not only by direct protonation but also by ligand switching, i.e., association of analytes in [H(H 2 O) n ] + water ion clusters followed by dissociation of water clusters [18,37].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…It has been implied for direct analysis in real time (DART) ionization that under typical ambient conditions water cluster formation is sufficiently rapid [6] to have no effect on ambient mass spectra. However, several research groups have used supplementary water with corona discharge APCI [19][20][21][22] to increase analyte MH + abundance. Large effects on mass spectra were also observed with DART of one analyte in a range of humidity values [23].…”
mentioning
confidence: 99%